Complex Postpartum Complication: ARDS Secondary to Candidemia and Utero-Cutaneous Fistula Following Cesarean Section - Prakash, Jyoti; B, Anil; Sharma, Tanushree (Achievements and Challenges of Medicine and Medical Science Vol. 11, 2025)
Candidemia, the systemic spread of Candida spp. is a significant concern in intensive care units and among immunocompromised patients. Clinical manifestations can range from mild fever to septic shock, complicating differentiation from bacterial sepsis. This study highlights a complex and challenging clinical case involving ARDS secondary to candidemia, with an uncommon finding of a utero-cutaneous fistula post-LSCS. It provides valuable insights into the diagnostic and therapeutic challenges of managing nosocomial infections in resource-limited settings. Additionally, the case underscores the importance of multidisciplinary care and highlights gaps in diagnostic workup that could inform future clinical guidelines. This case report details a young postpartum female who developed persistent candidemia following a lower-segment cesarean section. Postoperatively, the patient experienced a high-grade fever, respiratory distress, and disorientation, initially managed with broad-spectrum antibiotics and later with antifungal therapy. High-resolution computed tomography (HRCT) revealed ground-glass opacities in bilateral lung fields indicative of acute respiratory distress syndrome (ARDS). Blood Cultures confirmed Candida glabrata and imaging revealed a likely utero-cutaneous fistula as the infection source. Despite initial monotherapy, the patient showed no improvement, prompting the addition of a second antifungal agent. The dual regimen of Caspofungin and Voriconazole led to clinical improvement and subsequent blood cultures were sterile. The patient was discharged on oral fluconazole. This case underscores the complexities of managing persistent candidemia, particularly in the postpartum period, and highlights the potential benefits of dual-antifungal therapy in refractory cases. Comprehensive imaging and a multidisciplinary approach were crucial in identifying and managing the uncommon source of infection. The utero-cutaneous fistula was also noted which is a rare entity. This report contributes to the limited literature on postpartum candidemia and emphasizes the need for thorough evaluation and tailored treatment strategies. Further research is needed to establish clear guidelines regarding the use of combination antifungal therapy in the management of persistent candidemia and its complications such as utero-cutaneous fistula and to explore the management of complex cases involving uncommon sources of infection.